Effects of flavanols and procyanidins-rich cocoa consumption on metabolic syndrome: an update review (2013-2023) - Salaish Kumar, Sharvintha; Mhd Jalil, Abbe Maleyki; Hussin, Napisah; Mat Daud, Zulfitri Azuan (Oxford University Press, 2024)
Studies indicated that cocoa-based products effectively mitigate the risks associated with metabolic syndrome (MetS), however, the effect varies based on cocoa types, dosages, and study durations. This review aimed to determine the flavanol-rich cocoa consumption on MetS outcomes within the last decade (2013-2023), adhering to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Seven randomized-controlled trials (RCTs) used cocoa-based products containing 0.3-1680 mg flavanol monomers and 3.5-1270 mg procyanidins. Cocoa-based products beneficially reduced glycemic response, blood pressure and lipid profiles. However, this review highlights little evidence pinpointing the best cocoa products type and required dosage for the observed effects. Further intervention aiming to improve MetS should justify the selection and concentration of flavanols (monomers and procyanidins). A robust study design should consider registering the trials before study commencement, consider multicenter RCT trials, and adjust for potential covariates that might "masked"the outcomes.